The Effect of Compost and KCl Fertilizer Dosage on the Growth and Productivity of Sweet Corn : Zea mays Saccharata Sturt L - Zeni Abdi; Sudarma. JA; Ibnu Hajar (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aimed to evaluate the effect of compost fertilizer and potassium chloride (KCl) fertilizer, as well as their interaction, on the growth and yield of sweet corn (Zea mays saccharata Sturt). The experiment was conducted from May to August 2022 in Kuning Village, Bambel District, Southeast Aceh, using a factorial randomized block design with two factors: compost dosage (480 g/plot, 960 g/plot, 1,440 g/plot) and KCl dosage (20 g/plot, 40 g/plot, 60 g/plot), each replicated three times for a total of 27 plots. Observed parameters included plant height, stem diameter, leaf area, days to flowering, ear length, and ear weight per plot. Results indicated that compost and KCl fertilizers significantly affected plant height, leaf area, days to flowering, and ear length, but had no significant effect on stem diameter or ear weight per plot. The interaction between compost and KCl produced the highest plant height (165.89 cm) and ear length (21.69 cm) in treatment K3C1. The findings suggest that optimal fertilization using compost and KCl can enhance sweet corn productivity by improving vegetative growth and reproductive development. Nevertheless, the absence of significant effects on stem diameter and ear weight per plot indicates that nutrient balance, especially nitrogen (N) and phosphorus (P), remains crucial for maximizing yields. Therefore, integrating compost and KCl with complementary sources of macronutrients could promote more consistent outcomes. This research also highlights the role of organic matter in enriching soil fertility, maintaining soil structure, and supporting sustainable agriculture. The combination of organic and inorganic fertilizers demonstrates the potential for eco-friendly crop management practices that balance productivity with environmental responsibility. These results provide valuable insights for farmers, agronomists, and policymakers in developing efficient fertilization strategies for sweet corn cultivation within local conditions.